Do Injury Rates in Position Players Who Convert to Pitchers in Professional Baseball Differ From Players Who Have Always Been Pitchers?. Issue 10 (22nd October 2021) - Erickson, Brandon J.; Chalmers, Peter N.; D'Angelo, John; Ma, Kevin; Rowe, Dana; Ahmad, Christopher S.
Background: There are some professional baseball players who begin their career as a position player and later convert to a pitcher; injury rates in these players are unknown. Purpose: To compare injury rates of professional baseball players who started their career as position players and converted to pitchers with a control group of pitchers who have been only pitchers throughout their professional career. Hypothesis: Injury rates would be lower in the conversion players. Study Design: Cohort study; Level of evidence, 3. Methods: All players who began their professional baseball career as position players and converted to pitchers between 2011 and 2018 were included. All injuries that occurred after they converted to pitchers were included. The conversion players were matched 1 to 1 with a control group of pitchers who entered professional baseball as pitchers and never changed position. Injury rates were compared between groups. The performance between groups was also compared. Results: Overall, 221 players were identified who converted from position players to pitchers. There were significantly more injuries per year in the control pitcher group (0.8 ± 0.9) than in the conversion pitcher group (0.7 ± 0.9; P = .015). Injuries in the control group resulted in 61 ± 112 days missed per injury, while injuries in the conversion player group resulted in 54 ± 102 days missed per injury ( P = .894). Injury characteristics differed between groups. However, in both groups, most of the injuries were related to pitching or throwing, were noncontact or gradual overuse injuries, and involved the upper extremity. Converted pitchers had lower pitcher usage, with fewer games and innings pitched ( P < .001), with significantly worse statistics for walks plus hits per inning pitched ( P = .018). Conclusion: Professional baseball players who convert from position players to pitchers are injured at lower rates than control pitchers. Conversion pitchers have lower pitcher usage, which may contribute to their reduced injury rates.